Neutrophil activation and resistance to recombinant human erythropoietin therapy in Hemodialysis Patients - Costa, Elísio (2011)
The aim of this work was to evaluate the neutrophil activation state in chronic kidney disease (CKD) patients under hemodialysis, and its linkage with resistance to recombinant human erythropoietin (rhEPO) therapy. Methods: We studied 63 CKD patients under hemodialysis and rhEPO treatment (32 responders and 31 non-responders to rhEPO therapy). In 20 of the CKD patients (10 responders and 10 non-responders to rhEPO therapy), blood samples were also collected immediately after dialysis. Twenty-six healthy volunteers were included in a control group. Hemoglobin levels, total and differential leukocyte counts, and circulating levels of C-reactive protein (CRP), elastase and lactoferrin were measured in all patients and controls. Results: Compared with controls, CKD patients presented with significantly higher CRP, neutrophil and elastase levels. When we compared the 2 groups of patients, we found that non-responders presented statistically significantly higher elastase plasma levels. A positive significant correlation was found between elastase levels and weekly rhEPO dose and CRP serum levels. After the hemodialysis procedure, a statistically significant rise in elastase, lactoferrin and, elastase/neutrophil and lactoferrin/neutrophil ratios were found. Conclusions: Our data show that CKD patients under hemodialysis present higher elastase levels (particularly in non-responding patients), which could be related to the rise in neutrophils, and to be part of the enhanced inflammatory process found in these patients